Chronic Water-Pipe Smoke Exposure Induces Injurious Effects to Reproductive System in Male Mice - Ali, Badreldin H.; Al Balushi, Khalid A.; Ashique, Mohammed; Shalaby, Asem; Al Kindi, Mohammed A.; Adham, Sirin A.; Karaca, Turan; Beegam, Sumaya; Yuvaraju, Priya; Nemmar, Abderrahim (Frontiers in Physiology, 2017)
There is a global increase in the popularity of water-pipe tobacco smoking including Europe and North America. Nevertheless, little is known about the male reproductive effects of water-pipe smoke (WPS), especially after long-term exposure. Here we assessed effects of WPS exposure (30 min/ day) in male mice for 6 months. Control mice were exposed to air-only for the same period of time. Twenty-four h after the last exposure, testicular histopathology and markers of inflammation and oxidative stress, and the tyrosine - protein kinase vascular endothelial growth factor receptor 1 (VEGFR1) were assessed in testicular homogenates. Moreover, plasma testosterone, estradiol and luteinizing hormone (LH) concentrations were also measured. Chronic WPS exposure induced a significant decrease of testosterone and estradiol, and a slight but significant increase of LH. Glutathione reductase, catalase and ascorbic acid were significantly decreased following WPS exposure. Plasma concentration of leptin was significantly decreased by WPS exposure, whereas that of tumor necrosis factor α and interleukin 6 was significantly increased. Histopathological analysis of the testes revealed the presence of a marked reduction in the diameter of the seminiferous tubules with reduced spermatogenesis. Transmission electron microscopy examination showed irregular thickening and wrinkling of the basement membranes with abnormal shapes and structures of the spermatozoa. VEGFR1 was overexpressed in the testis of the mice exposed to WPS and was not detected in the control. The urine concentration of cotinine, the predominant metabolite of nicotine, was significantly increased in the WPS-exposed group compared with the control group. We conclude that chronic exposure to WPS induces damaging effects to the reproductive system in male mice. If this can be confirmed in humans, it would be an additional concern to an already serious public health problem, especially with the increased use of WPS use all over the world, especially in young adults.